2012
DOI: 10.1111/rda.12107
|View full text |Cite
|
Sign up to set email alerts
|

Lactate in Bitches with Pyometra

Abstract: Contents Lactate is a compound produced by the anaerobic metabolism of glucose, and hyperlactataemia occurs when the rate of production of lactate exceeds the rate of elimination. This occurs in situations of hypoxia and tissue hypoperfusion. Lactate has been considered a useful prognostic indicator in critically ill patients. Pyometra is a disease of adult female dogs characterized by inflammation of the uterus with an accumulation of exudate, which occurs during the luteal phase. It is one of the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Lactate has been used as a parameter for evaluation of inflammation status in dogs ( 12 , 28 , 29 ). Hyperlactatemia is common in emergency and clinical critical care and occurs with evidence of tissue oxygen deficiency and systemic hypoperfusion ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate has been used as a parameter for evaluation of inflammation status in dogs ( 12 , 28 , 29 ). Hyperlactatemia is common in emergency and clinical critical care and occurs with evidence of tissue oxygen deficiency and systemic hypoperfusion ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlactatemia is common in emergency and clinical critical care and occurs with evidence of tissue oxygen deficiency and systemic hypoperfusion ( 28 ). In human medicine, lactate has shown prognostic value in systemic inflammatory response syndrome (SIRS), and recent studies revealed that hypoxia, inflammation, viral infection, and tumors promote the production of lactate, which may act to modulate the immune-inflammatory response ( 29 31 ). In accordance with the findings of previous studies, lactate showed a significant difference between group B and the other groups ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, cells are forced to metabolize glucose anaerobically, which leads to lactate formation. Therefore, elevated lactate is indicative of tissue hypoxia, hypoperfusion and possible damage (Volpato et al, 2012). The increment of lactic acid is evidenced by the duplication of LDH enzyme activities in zinc deficient lambs.…”
Section: Ajavsmentioning
confidence: 99%
“…Hyperlactatemia and lactic acidosis occur commonly in veterinary patients and have been extensively studied in clinical disorders such as shock, low cardiac output, acute liver failure, sepsis, neoplasia and seizures (1)(2)(3)(4). It is beyond the scope of this paper to review lactate physiology and pathophysiology but an in-depth discussion on lactate metabolism has been published previously (2).…”
Section: Introductionmentioning
confidence: 99%